2008
DOI: 10.1142/s0192415x08006004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tianma Gouteng Decoction with Subtractive Ingredients and Its Active Constituents on Memory Acquisition

Abstract: Accumulating evidence indicates that the high blood pressure (BP) is a potent risk factor for dementia in the elderly. In line with this theory, we had found the mixture of Chinese herbs (TGD) which were traditionally used to treat hypertension, could enhance the cognitive function. The aim of this study was to decrease the number of herbs used from 11 (TGD) to 4 herbs (TGDS) and further to search the active constituents. After administering a dose of 10 g/kg of TGDS0 to ICR mice, no cholinergic symptoms of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…For instance, Gouteng has been traditionally used alongside with Tianma in treating high blood pressure (63). A recent study has illustrated that the use of Tianma and Gouteng with two other herbs has anti-hypertensive effects and shows an enhancing effect on cognitive functions and thus, taken our results into account, could be used against cognitive defects and dementia (8,9). However, the complexity and multi-actions of herbal bioactive compounds remain unclear.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For instance, Gouteng has been traditionally used alongside with Tianma in treating high blood pressure (63). A recent study has illustrated that the use of Tianma and Gouteng with two other herbs has anti-hypertensive effects and shows an enhancing effect on cognitive functions and thus, taken our results into account, could be used against cognitive defects and dementia (8,9). However, the complexity and multi-actions of herbal bioactive compounds remain unclear.…”
Section: Discussionmentioning
confidence: 84%
“…Mice (C57BL/6J) were randomly assigned to control and Tianma-treated groups (10 each, 5 male, 5 female). According to previous reports and our own recent studies, the average daily dose of Tianma per mouse was 2.5 g/kg body weight (7)(8)(9)(10). Feeding was done orally with a blunt needle syringe by dispensing the Tianma solution drop by drop for the period of two months.…”
Section: Animal Materialsmentioning
confidence: 97%
“…For example, by using experimental stroke animal models and conducting clinical trials, tianma gouteng decoction, a representative formula for the treatment of primary hypertension and transient ischemic attack, revealed to decrease blood pressure, ameliorate cognitive impairment and protect neural cells in ischemic brains [63,64,65]. Due to the poor design of clinical trials, however, a recent systematic review challenged its clinical efficacy for the treatment of primary hypertension [66].…”
Section: Classic Concepts and Representative Therapeutics For Stroke mentioning
confidence: 99%
“…It has been described by the Chinese Pharmacopoeia as an analgesic that can be used in the treatment of dizziness, hypertension, convulsion, epilepsy, vertigo and stroke [9][10][11] . Studies have reported that tianma has antioxidant, anti-inflammatory, anti-angiogenic properties [12,13] in addition to possessing neuroprotective effects [14][15][16] . In one study conducted by Mishra et al [17] , mice stimulated with tianma showed improved cognitive functions and learning capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In one study conducted by Mishra et al [17] , mice stimulated with tianma showed improved cognitive functions and learning capacity. Based on these studies, tianma's neuroprotective roles and its ability to enhance learning and memory capabilities [13] have highlighted its potential as a therapeutic agent for neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%